2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Kuhn, Jens H.; Alioto, Daniela; Amarasinghe, Gaya K.; Anthony, Simon J.; Avšič-Županc, Tatjana; Ayllón, María A.; Balkema-Buschmann, Anne; Ballinger, Matthew J.; Basler, Christopher; Bavari, Sina; Beer, Martin; Bente, Dennis A.; et al. (Archives of virology, 2020)
In March 2020, following the annual International Committee on Taxonomy of Viruses (ICTV) ratification vote on newly proposed taxa, the phylum Negarnaviricota was amended and emended. At the genus rank, 20 new genera were added, two were deleted, one was moved, and three were renamed. At the species rank, 160 species were added, four were deleted, ten were moved and renamed, and 30 species were renamed. This article presents the updated taxonomy of Negarnaviricota as now accepted by the ICTV.